Using mouse strokes to verify user identity - Toh, Jing Sheng. (2013)
As the technology advances, many interesting approaches have emerged to tackle the flaw of the traditional authentication techniques which verify users based on something that one knows or possesses. Not only do these systems expose their users to identity theft, users could also forget their password or misplace the hardware token used for authentication. Many new approaches involve the use of biometric authentication which is based on inherent and unique characteristics of the user.